Pragmatic Competence: Its Role in Language Acquisition and Teaching Strategies - Amon Bernabas Tenis (CV Alifba Media, 2024)
This study explores the critical role of pragmatic competence in language acquisition and its implications for teaching strategies. Pragmatic competence involves using language appropriately in various social contexts, an essential skill often overlooked in traditional language instruction. The study employed a mixed-methods approach, with both quantitative and qualitative data collected from intermediate-level learners. Results indicated a significant improvement in the pragmatic abilities of learners who received explicit instruction, compared to those following a standard curriculum. The study highlights the importance of integrating pragmatic elements such as speech acts, conversational management, and cultural norms into language teaching curricula. Challenges include the lack of appropriate teaching materials and teacher training. The findings suggest that addressing these challenges can significantly enhance language learners' communicative competence, equipping them for real-world interactions. This study contributes to the growing emphasis on pragmatic competence in language education and calls for a more comprehensive approach to teaching pragmatics across all proficiency levels.